2017
DOI: 10.3389/fphar.2017.00425
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Minimum Inhibitory Concentrations of Rhubarb Water Extracts Inhibit Streptococcus suis Biofilm Formation

Abstract: Streptococcus suis is one of the most important swine pathogens, which can cause persistent infection by forming biofilms. In this study, sub-minimum inhibitory concentration (sub-MIC) of rhubarb water extracts were found to inhibit biofilm formation. Two-component signal transduction systems (TCSs), transcriptional regulators, and DNA binding proteins were compared under two conditions: (1) cells treated with sub-MIC rhubarb water extracts and (2) untreated cells. Using an isobaric tags for relative and absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…A previous study from our laboratory observed that the water extract of R. o cinale can intervene with the bio lm formation of S.suis [37]. However, it is not clear which ingredients from R. o cinale played the major role in this process.…”
Section: Introductionmentioning
confidence: 87%
“…A previous study from our laboratory observed that the water extract of R. o cinale can intervene with the bio lm formation of S.suis [37]. However, it is not clear which ingredients from R. o cinale played the major role in this process.…”
Section: Introductionmentioning
confidence: 87%
“…Specific methods of iTRAQ-based quantitative proteomic analyses were conducted using a method similar to that described in the literature [22]. In brief, the sample was lysed[23] followed by homogenisation; proteins in the sample were run on a sodium dodecyl sulphate polyacrylamide gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, control (with TSB alone) and negative control (with bacteria alone) were included after incubation at 37°C for 24 h without shaking. The supernatant was removed, the wells were rinsed three times with phosphate-buffered saline (PBS; pH 7.2), 200 μL of 99% methanol was added to the wells to fix the biofilms, and then, the plates were emptied after 15 min and stained for 5 min with 200 μL of 2% crystal violet per well ( Ding et al, 2017 ). The wells were rinsed with PBS (pH 7.2), and the dye was resolubilized with 200 μL of 33% (v/v) glacial acetic acid per well ( Ding et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was removed, the wells were rinsed three times with phosphate-buffered saline (PBS; pH 7.2), 200 μL of 99% methanol was added to the wells to fix the biofilms, and then, the plates were emptied after 15 min and stained for 5 min with 200 μL of 2% crystal violet per well ( Ding et al, 2017 ). The wells were rinsed with PBS (pH 7.2), and the dye was resolubilized with 200 μL of 33% (v/v) glacial acetic acid per well ( Ding et al, 2017 ). All wells were then measured using a Tecan GENios Plus microplate reader (Tecan, Austria) at 595 nm ( Ding et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%